Medical Imaging 2017: Physics of Medical Imaging 2017
DOI: 10.1117/12.2254120
|View full text |Cite
|
Sign up to set email alerts
|

Real time implementation of anti-scatter grid artifact elimination method for high resolution x-ray imaging CMOS detectors using Graphics Processing Units (GPUs)

Abstract: Scatter is one of the most important factors effecting image quality in radiography. One of the best scatter reduction methods in dynamic imaging is an anti-scatter grid. However, when used with high resolution imaging detectors these grids may leave grid-line artifacts with increasing severity as detector resolution improves. The presence of such artifacts can mask important details in the image and degrade image quality. We have previously demonstrated that, in order to remove these artifacts, one must first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previously it was shown that by first subtracting the residual scatter from the image and then by logarithmic subtraction of the reference image of the grid, grid artifacts can be eliminated [2,3]. The residual scatter was recursively derived from an initial scatter estimate obtained by placing lead beads on the test object being imaged.…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was shown that by first subtracting the residual scatter from the image and then by logarithmic subtraction of the reference image of the grid, grid artifacts can be eliminated [2,3]. The residual scatter was recursively derived from an initial scatter estimate obtained by placing lead beads on the test object being imaged.…”
Section: Introductionmentioning
confidence: 99%